Relationship between calcium and magnesium intake and blood pressure in adulthood - Dwi Lestari (Ilmu Gizi Indonesia, 2019)
Background: Hypertension occurs due to environmental factors, genetic factors and interactions between them. Environmental factors affected the most on blood pressure are food or dietary, which it plays the most important role in blood pressure homeostasis. Calcium and magnesium levels in the blood are important because calcium makes the heart contract, while magnesium functions to help the heart muscle for relaxation. Objective: This study aimed to determine the relationship between calcium and magnesium intake and blood pressure at age 18 ̶ 44 years in Kedungkandang, Malang. Methods: This was cross-sectional study with consecutive samplingon the sample of 90 people. Calcium and magnesium intakeswere obtained using weighing food record and 24-hours food recall. Blood pressure was measured using a mercury sphygmomanometer. Bivariate analysis was performed by Spearman Rank Correlation test. Results: There was no significant relationship between calcium intake and systolic and diastolic blood pressure (p>0.05). Between magnesium intake and systolic blood pressures showed a significant relationship (p=0.005, r=0.207), butfor diastolic blood pressure had nosignificant relationship (p>0.05). Daily average of calcium intakewas 208.5±123 mg and magnesium intake was 226.2±110.2 mg. Conclusion: There was a significant relationship between magnesium intake and systolic blood pressure, but the closeness of the relationship was weak and positive, meaning that the higher magnesium intake the higher systolic blood pressure. On the other hand, there was no significant relationship between calcium intake and systolic and diastolic blood pressure.